Assessing the efficacy of coproduction to better understand the barriers to achieving sustainability in NHS chronic kidney services and create alternate pathways. (28th December 2021) - Mc Laughlin, Leah; Williams, Gail; Roberts, Gareth; Dallimore, David; Fellowes, David; Popham, Joanne; Charles, Joanna; Chess, James; Williams, Sarah Hirst; Mathews, Jonathan; Howells, Teri; Stone, Judith; et al.
Abstract: Context: Too many people living with chronic kidney disease are opting for and starting on hospital‐based dialysis compared to a home‐based kidney replacement therapy. Dialysis services are becoming financially unsustainable. Objective: This study aimed to assess the efficacy of coproductive research in chronic kidney disease service improvement to achieve greater sustainability. Design: A 2‐year coproductive service improvement study was conducted with multiple stakeholders with the specific intention of maximizing engagement with the national health kidney services, patients and public. Setting and Participants: A national health kidney service (3 health boards, 18 dialysis units), patients and families ( n  = 50), multidisciplinary teams including doctors, nurses, psychologists, social workers, and so forth ( n  = 68), kidney charities, independent dialysis service providers and wider social services were part of this study. Findings: Coproductive research identified underutilized resources (e.g., patients on home dialysis and social services) and their potential, highlighted unmet social care needs for patients and families and informed service redesign. Education packages were reimagined to support the home dialysis agenda including opportunities for wider service input. The impacts of one size fits all approaches to dialysis on specialist workforce skills were made clearer and also professional, patient and public perceptions of key sustainability policies. Discussion and Conclusions: Patient and key stakeholders mapped out new ways to link services to create more sustainable models of kidney health and social care. Maintaining principles of knowledge coproduction could help achieve financial sustainability and move towards more prudent adult chronic kidney disease services. Patient or Public Contribution: Involved in developing research questions, study design, management and conduct, interpretation of evidence and dissemination.